2021
DOI: 10.1039/d1dt03239a
|View full text |Cite
|
Sign up to set email alerts
|

A counterion study of a series of [Cu(P^P)(N^N)][A] compounds with bis(phosphane) and 6-methyl and 6,6′-dimethyl-substituted 2,2′-bipyridine ligands for light-emitting electrochemical cells

Abstract: The choice of counterion in heteroleptic copper(i) luminophores for LECs has a critical effect on the photoluminescence quantum yields of the solid materials, and on the device figures-of-merit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 98 publications
4
22
0
Order By: Relevance
“…The reduction processes for compounds 1 − 5 were poorly resolved, while 6 demonstrates reversible reduction at a potential of −1.7 V. Due to the irreversibility of the oxidation processes, differential pulse voltammetry (DPV) ( Figure S19 ) was used to determine the precise values of the oxidation potentials, and further DPV data will be analyzed. The first oxidation potentials, (1) ( Table 1 ), for compounds 1 − 4 and 6 are close to 0.8 V vs. Fc/Fc + , while the voltammogram of the oxidation of compound 5 contains a less pronounced peak at 0.72 V. It indicates that the metal-centred oxidation processes of complexes 1 − 6 are similar to each other and the Cu + /Cu 2+ transition potential is close to that observed in similar complexes (0.8 V vs. Fc/Fc + ) [ 23 , 24 , 25 , 26 , 27 , 29 , 30 , 35 , 37 , 45 , 46 , 47 ]. The low intensity of the first oxidation peak in the complex 5 indicates that metal oxidation is suppressed, possibly, due to sterical reasons.…”
Section: Resultsmentioning
confidence: 72%
“…The reduction processes for compounds 1 − 5 were poorly resolved, while 6 demonstrates reversible reduction at a potential of −1.7 V. Due to the irreversibility of the oxidation processes, differential pulse voltammetry (DPV) ( Figure S19 ) was used to determine the precise values of the oxidation potentials, and further DPV data will be analyzed. The first oxidation potentials, (1) ( Table 1 ), for compounds 1 − 4 and 6 are close to 0.8 V vs. Fc/Fc + , while the voltammogram of the oxidation of compound 5 contains a less pronounced peak at 0.72 V. It indicates that the metal-centred oxidation processes of complexes 1 − 6 are similar to each other and the Cu + /Cu 2+ transition potential is close to that observed in similar complexes (0.8 V vs. Fc/Fc + ) [ 23 , 24 , 25 , 26 , 27 , 29 , 30 , 35 , 37 , 45 , 46 , 47 ]. The low intensity of the first oxidation peak in the complex 5 indicates that metal oxidation is suppressed, possibly, due to sterical reasons.…”
Section: Resultsmentioning
confidence: 72%
“…14 Overviews of [Cu(N^N)(P^P)] + emitters 10,11 reveal that some of the most efficient copper-based LECs have been fabricated using [Cu(6,6′-Me 2 bpy)(xantphos)][PF 6 ], 15 [Cu(4,5,6-Me 3 bpy) (xantphos)][PF 6 ], 16 and [Cu(4,4′-(CF 3 ) 2 -6,6′-Me 2 bpy) (xantphos)][PF 6 ]. 17 Compounds for which high values of the solid-state photoluminescence quantum yields (PLQYs) have been found include [Cu(4,4′,6,6′-Me 4 bpy)(POP)][BF 4 ] (55% or 74%, depending on whether the sample was ground), 18 [Cu(6-Mebpy)(xantphos)][PF 6 ] (34%), 15 [Cu(6-Etbpy)(xant-phos)][PF 6 ] (37%), 15 and [Cu(6,6′-Me 2 bpy)(xantphos)][PF 6 ] (37% 15 or 62%, 19 the difference again being attributed to sample morphology). Although we recently demonstrated that the introduction of long and potentially sterically demanding 6-substituents into the bpy domain was not detrimental to the photophysical properties, 20 it appears that few investigations have considered substituents longer than an ethyl chain.…”
Section: Introductionmentioning
confidence: 99%
“…19,30,[38][39][40][41][42][43][44][45][46] Second, the introduction of substituents at the ortho positions of the a-diimine coordination sites is a good way to gain better emission, because it can increase the steric hindrance of the coordination sites and reduce the quenching of luminescence caused by the attack of solvent molecules, especially water molecules. 4,15,37,[47][48][49][50][51] For instance, a highly luminescent Cu(I) complex has been reported by introducing two methyl groups to the 6,6 0 -positions of 4,4 0dimethyl-2,2 0 -bipyridine (dmbpy). 37 Its luminescence quantum yield was 6 times that of the Cu(I) analogue with dmbpy.…”
Section: Introductionmentioning
confidence: 99%
“…Since the groundbreaking work of α-diimine-Cu( i )–phosphine complexes with the earth-abundant and environmentally benign metal copper was reported by McMillin's group in the late 1970s, 1,2 these systems have attracted more and more attention because of their good room temperature phosphorescence in the solid state, long luminescence lifetime and tunable emission, 3–35 followed by the corresponding applications in organic light-emitting diodes (OLEDs), 11,13,24–27 bioimaging, 28 chemosensors, 10,29–32 and photocatalysis. 14,18,33–35 In recent years, the thermally activated delayed fluorescence (TADF) exhibited by α-diimine-Cu( i )–phosphine complexes led to their further development into a research boom.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation